Assessing the Competence of Prospective Early Childhood Teachers in Facilitating English Learning through Storytelling - Wahab, Aulia Dwi Amalina; Sativa, Filsa Era; Arqi, Muh. Amin (GENIUS: Indonesian Journal of Early Childhood Education, 2025)
This study examines the competence of prospective early childhood education teachers in facilitating English language learning through storytelling. Employing a qualitative descriptive approach with a case study design, the research involved 20 purposively selected participants from a cohort of 112 students. Data were gathered through video observations of storytelling sessions and analyzed across four dimensions: story preparation, language use, vocabulary introduction, and child engagement. The results indicate that most participants demonstrated adequate competence in selecting age-appropriate stories (80%), using suitable English (70%), and engaging children through expressive techniques (85%). However, notable weaknesses were observed in vocabulary reinforcement (60%) and maintaining consistent tempo and intonation during delivery (70%). These findings highlight the need for targeted pedagogical training in storytelling as a method for early English instruction. The study recommends curriculum enhancements in teacher education programs to better equip future educators with practical strategies for effective, child-centered language learning.